Role of Interleukin 6 in Innate Immunity to Mycobacterium tuberculosis Infection - Martinez, Alejandra N. (Oxford University Press, 2013)
Background. Mycobacterium tuberculosis can grow in the hostile intracellular environment of macrophages by actively evading macrophage-associated antibacterial activities. The stress response factor SigH contributes to this process by modulating β-chemokine and interleukin 6 (Il6) expression. Hence, Il6 is of critical importance for acquired immunity against M. tuberculosis infection. Here, we attempted to better characterize the role of Il6 in the immune response to M. tuberculosis infection. Methods. A small interfering RNA–based approach was used to silence expression of the Il6 transcript in host macrophages infected with a wild-type strain of M. tuberculosis or an attenuated mutant strain of M. tuberculosis (Mtb:Δ-sigH). The outcome was measured by the analysis of bacterial burden and transcriptome-wide analysis of host gene expression. Transcriptome results were confirmed via quantitative polymerase chain reaction and enzyme-linked immunosorbent assay. Results. Wild type and Mtb:Δ-sigH infection of host macrophages in which Il6 had been silenced resulted in increased expression of interferon-inducible genes, especially those involved in type I interferon signaling. The expression of Ly-6 genes was significantly higher in cells infected with Mtb:Δ-sigH, compared with those infected with the wild-type strain (P < .05). Conclusions. M. tuberculosis regulates host Il6 production to inhibit type I interferon signaling and, consequently, disease progression. Mtb:Δ-sigH is associated with delayed activation of macrophages, compared with the wild-type strain, and with delayed inflammatory stimuli as consequence. These findings have important implications for improving understanding of the mechanisms behind M. tuberculosis virulence and pathogenesis and provide an initial road map to further investigate the mechanisms that may account for the deleterious effects of type I interferons in M. tuberculosis infection.